Experimental analysis of fracture toughness and microstructure of extruded Al 6082-T6 alloy flats using compact tension specimens - Y. S. Upadhyaya; Amulya Peerla; Vishwanath Managuli (Cogent Engineering)
The Al 6082-T6 alloy has extensive applications in diverse engineering domains, including automotive, aerospace, and construction. It is used in various industries owing to its superior strength and corrosion resistance. The analysis of fracture toughness and microstructure is essential for ensuring structural integrity and, therefore, to prevent failure. Because of its crucial role in determining the resistance of a material to fracture and crack propagation, the current study focuses on the experimental analysis of fracture toughness. This study examined the plane-strain fracture toughness of a flat, extruded Al 6082-T6 material. Compact Tension (CT) specimens of L-T type were prepared according to the ASTM E 399-90 standard. The fracture toughness value for Al 6082-T6 was determined as 19.52 MPa√m and is in line with the value obtained by other researchers under different conditions. Microstructural analysis distinctly identified ductile fracture failure. The estimated fracture toughness value, combined with a microstructure study, helps toward fracture-based design of Al 6082-T6 alloy used in industrial applications.